Sino-Singapore Tianjin Eco-City : A Case Study of an Emerging Eco-City in China - World Bank (Washington, DC, 2017)
China is experiencing rapid and large scale urbanization, and the resulting local and global urban environmental challenges are unprecedented. The Chinese Government has fully recognized these challenges and is aiming to promote more sustainable urbanization in line with the objectives of the eleventh five year plan, which calls for 'building a resource-conserving and environmentally friendly society'. Various initiatives are being pursued to support this objective, both at the national and local levels. At the local level, cities have responded by developing 'eco-cities', which aim to promote a more sustainable urbanization model. More than one hundred eco-city initiatives have been launched in recent years. One such initiative is the Sino-Singapore Tianjin eco-city. The purpose of this report is to review the Sino-Singapore Tianjin Eco-City (SSTEC) project from a comprehensive perspective with a view to achieving the following principal objectives: (i) create a detailed knowledge base on the project; (ii) provide policy advice on key issues, especially those related to the Global Environment Facility (GEF) project; (iii) estimate SSTEC's Greenhouse Gas (GHG) emission reduction potential; and (iv) contextualize the project among the broader ecological urban development initiatives in China. Broadening the World Bank's engagement beyond the GEF was assessed as important given the project's complexity, and its potential to shed light on China's sustainable urban development challenges